An elevator group control system with a self-tuning fuzzy logic group controller - Jamaludin, J.; Rahim, N.A.; Hew, W.P. (Institute of Electrical and Electronics Engineers (IEEE), 2010)
This paper presents a new group controller's adaptation mechanism with fuzzy logic for elevator group control system (EGCS) applications. Instead of depending heavily on the predicted passenger traffic pattern for adaptation, the fuzzy logic group controller (FLGC) adjusts itself to suit the system's environment through a self-tuning scheme. The average-waiting-time data that reflect the measured performance results of the EGCS are exploited to tune the membership functions of the input parameters and to modify the fuzzy rule sets employed by the FLGC, thus leading to better controller's performance and improved EGCS service quality. Computer simulation shows satisfactory improvements made in passenger waiting time and passenger riding time as compared to the performance of the conventional group controllers in three traffic peaks. The hardware implementation of the self-tuning FLGC on a TMS320C6416T digital signal processor further demonstrates its practicality.